Profile of High-Order Thinking Skills of Physics Teacher Prospective Students at the Cognitive Level of Evaluation and Creation - Nasir, Muhammad; Afkar, Rian (Asian Journal of Science Education, 2023)
High order thinking skills require not only the ability to remember, but also other higher abilities such as critical and creative thinking. These thinking skills are very important for teacher candidates to have as a provision for teaching in schools in the future. The research objective was to determine the profile of high order thinking skills of physics teacher prospective students at cognitive levels evaluation and creation. This research uses descriptive qualitative approach. The subjects of this study were 50 students of Physics Education Department UIN Ar-Raniry Banda Aceh who had programmed Basic Physics 1 course. Data was collected by giving written tests of description questions with evaluation and creation cognitive levels. The results of the data analysis showed that subjects had low high order thingking skills in solving evaluation questions and very low high order thingking skills in solving creation questions. At evaluation level, the subjects have not been able to apply a known concept to solve the problems. At creation level, the subjects have not been able to connect the problems in the questions with the physics concepts must be used. Therefore, students must be accustomed to giving high order thinking questions in the learning process in class. Lecturers must also use appropriate learning methods to improve students' high order thinking skills.